Teaching Strategies, Learning Environments and Students’ Motivation to Learn English : PLS SEM Analysis - Tisa, Rosma; Melvina, Melvina; Ikhsan, M Khairi (Linguistics and ELT Journal, 2025)
In the learning process, teaching strategies and the learning environment play an important role in motivating students. Learning motivation is the foundation for developing learning potential optimally. However, students' motivation to learn English is still relatively low. This can be seen from various factors that influence low learning motivation, including difficulty in understanding English, lack of confidence, and lack of enthusiasm, such as frequently asking for permission to leave class, not submitting assignments on time, and sleeping in class. This research aims to analyze the influence of teacher teaching strategy and student learning environment on English learning motivation at SMP N 1 2 x 11 Enam Lingkung. A quantitative method was used in this study, with a sample of 68 Grade IX students. The study used questionnaires for data collection and the data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0 software. The findings show that teaching strategy and learning environment individually have a significant influence on English learning motivation. Simultaneously, teaching strategy and learning environment explain 57% of the variation in English learning motivation (R2 = 0.570), with the remaining 43% attributed to other factors not included in the model. This study concludes that Effective and varied teaching strategies, coupled with a conducive and supportive learning environment, are crucial for increasing student engagement and motivation in English language learning.